Investigation of the Brillouin effect in highly nonlinear hafnium bismuth erbium doped fiber - Ahmad, Aminah; Cheng, Xiau San; Paul, Mukul Chandra; Dhar, Anirban; Das, Shyamal; Ahmad, Harith; Harun, Sulaiman Wadi (John Wiley & Sons, 2019)
This paper demonstrates the generation of the Brillouin fiber laser (BFL) with 0.5 m long hafnium bismuth erbium doped fiber (HBEDF) as a hybrid gain medium. As the gain medium is pumped by a 980 nm laser diode at the power of 170 mW, a stable Stokes is observed at the output power of −2.96 dBm with Brillouin pump (BP) power of 3 dBm. The laser operates at wavelength shifted by 0.09 nm from the BP. To the best of the authors' knowledge, this is the first report of a compact BFL without employing any lengthy SMF, which features a simple cavity configuration.